Geocaching: A New Instructional Tool for Natural Resources Extension and Outreach - Jacob Smith; Dave Coyle; John Thomason; Todd Matthews; John J. Riggins ([TEST] Journal of Extension, 2021)
Nonnative pests and pathogens severely affect forest health and are often spread in firewood. Our objectives were to create an extension education program using “Don’t Move Firewood”-themed geocaches and travel bugs which were placed near campgrounds across Mississippi, and to assess the efficiency and effectiveness of this outreach method. Interactions with caches and travel bugs were monitored over nearly one year and summarized to provide a measure of outreach success. With a one-time per-unit cost of $45.95 for caches and $6.75 for travel bugs, these tools provide ongoing, cost-effective educational approaches well suited to augment existing or launch new outreach efforts.
Keywords: camping; citizen engagement; forest health; invasive species; outdoor recreation